Scattering preventive agent containing microfibrillated cellulose

The use of microfibril cellulose with an average fiber width greater than 1.0 μm in a shatterproofing agent addresses the issue of gelation in existing dust shattering agents, enabling stable high-concentration storage and easy dispensing with weak stirring, thus enhancing operational efficiency and reducing costs.

JP2025054066AActive Publication Date: 2025-04-07NIPPON PAPER IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023163250
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

Existing dust shattering agents, such as those containing fine fibrous cellulose, tend to gel over time, requiring strong stirring or dispersion treatments for redispersion, which can lead to clogging and difficulty in dispensing, especially when stored at high concentrations.

Method used

A shatterproofing agent is developed using microfibril cellulose with an average fiber width greater than 1.0 μm and a solvent, which maintains a stable dispersion even at high concentrations and can be easily diluted and dispensed with weak stirring.

Benefits of technology

The microfibril cellulose-based shatterproofing agent effectively prevents dust scattering while remaining non-gelative at high concentrations, allowing for easy and cost-effective transportation, storage, and on-site use without the need for strong agitation equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054066000001_ABST
    Figure 2025054066000001_ABST
Patent Text Reader

Abstract

To provide a scattering preventive agent that uses cellulose-derived materials, and, while having good scattering prevention effects, is resistant to gelling even when stored at high concentrations, and can be easily discharged in a good state with relatively low stirring force during dilution.SOLUTION: A scattering preventive agent is made using microfibrillated cellulose with an average fiber width larger than 1.0 μm and a solvent. The microfibrillated cellulose may be chemically modified microfibrillated cellulose. Additionally, the scattering preventive agent can also be used to prevent the scattering of organic multi-materials.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a shatterproofing agent containing microfibril cellulose and a solvent. [Background technology]

[0002] Sand blown from the ground surface and dust scattered from construction sites, metal mining sites, reclaimed land, building sites, waste disposal sites, various factories, etc., have a negative impact on the working environment and the surrounding environment. For this reason, measures to prevent dust from scattering are taken by sprinkling water or covering areas where dust may be generated with sheets or nets. Liquid dust-scattering inhibitors are also sometimes sprayed.

[0003] For example, Patent Document 1 discloses a dust-scattering prevention agent that contains a solvent and fibrous cellulose having a fiber width of 1000 nm or less, and discloses that the dust-scattering prevention effect can be obtained by spray-coating (atomizing coating) this agent onto a dust-generating object. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-155738 Summary of the Invention [Problem to be solved by the invention]

[0005] In the examples of Patent Document 1, it is described that an aqueous dispersion of fine fibrous cellulose (CNF) with a concentration of 0.4% by mass was used as a scattering prevention agent and sprayed using a commercially available sprayer. The inventors have studied the scattering prevention agent described in the examples of Patent Document 1, and found that it can be sprayed with a sprayer immediately after the production of fine fibrous cellulose (not long after a strong dispersion treatment such as a high-pressure homogenizer or wet-type atomizer), but gelation progresses as time passes after production, so strong stirring or strong dispersion treatment is required for redispersion before use. If the dispersion power before use is weak, gel-like lumps remain, clogging the sprayer, or lumps remain at the bottom of the sprayer, making it difficult to discharge the entire amount. Furthermore, this tendency was more pronounced when the agent was stored at a higher concentration (for example, 2% by mass) and then diluted for use. Considering the costs of transporting and storing the anti-scattering agent, it would be desirable to prepare a high concentration of the agent in advance and dilute it at the site where the agent is to be used. However, such sites often do not have equipment capable of performing strong mixing or strong dispersion treatment, so it is difficult to store the anti-scattering agent of Patent Document 1 at a high concentration and dilute it at the site.

[0006] The present invention aims to provide a shatterproofing agent that uses a material derived from cellulose, is resistant to gelling even when stored at a high concentration, and can be made into a state that can be easily discharged with a relatively weak stirring force when diluted for use. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that by using microfibril cellulose having an average fiber width of more than 1.0 μm to produce a shatterproof agent, it is possible to produce a shatterproof agent that maintains the same shatterproof effect as the shatterproof agent of Patent Document 1, is resistant to gelling even when stored at high concentration, and can be made into a state that can be easily discharged by weak stirring when diluted from a high concentration state to a concentration suitable for use. Examples of the present invention include, but are not limited to, the following. (1) A shatterproof agent comprising microfibril cellulose having an average fiber width of greater than 1.0 μm and a solvent. (2) The shatterproof agent according to (1), wherein the microfibril cellulose is chemically modified microfibril cellulose. (3) The shatterproof agent according to (1) or (2), wherein the microfibril cellulose has a transmittance of 60% or less for light having a wavelength of 660 nm when dispersed in water at 1.0% by mass. (4) The shatterproof agent according to any one of (1) to (3), wherein the solvent contains water in an amount of 50% by mass or more when the entire solvent is taken as 100% by mass. (5) The shatterproof agent according to any one of (1) to (4), containing the microfibril cellulose in an amount of 0.5 to 2.5% by mass. (6) A scattering prevention agent according to any one of (1) to (5) for preventing scattering of organic mulch materials. (7) Providing microfibril cellulose having an average fiber width of greater than 1.0 μm; Preparing a dispersion containing the microfibril cellulose at a concentration of greater than 2.5% by mass; leaving the dispersion liquid for 30 minutes or more without stirring; diluting the dispersion that has been left standing so that the concentration of the microfibril cellulose becomes 0.5 to 2.5% by mass, and stirring the diluted dispersion; and The dispersion liquid after the stirring process is sprayed toward an object to be prevented from scattering. The shatterproof method includes: (8) Use of microfibril cellulose having an average fiber width of more than 1.0 μm for producing a shatterproof agent. Effect of the Invention

[0008] The shatterproofing agent of the present invention has the advantage that, while having a good shatterproofing effect, it is difficult to gel even when stored at a high concentration, and when diluting from a high concentration to a concentration suitable for use, it can be made into a state that can be discharged well by weak stirring. Cellulose fibers with a fine diameter are generally produced by wet fiberization of pulp and are often shipped in the form of a slurry. In this case, since the cost increases when transporting and storing at a low concentration, it is advantageous in terms of cost to make the slurry as high concentration as possible. The shatterproofing agent using the cellulose-derived material of the present invention is difficult to gel even when stored at a high concentration, and weak stirring is sufficient for redispersion when diluted, compared to the conventional shatterproofing agent using fine fibrous cellulose (CNF). Therefore, it is advantageous in terms of cost, and can be easily diluted and used even at sites where there is no equipment for strong stirring treatment, and has the advantage of improving workability at the site. [Brief description of the drawings]

[0009] [Figure 1] This is a photograph showing the dispersion state of the MFC dispersion and CNF dispersion immediately after stirring at 1000 rpm for 30 seconds in Example 1. [Diagram 2] 13 shows photographs of the containers from above after blowing air into them for test numbers 1 to 4 in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention relates to a shatterproofing agent containing microfibril cellulose (hereinafter, microfibril cellulose will be referred to as "MFC") having an average fiber width of more than 1.0 μm and a solvent. The present invention is based on the discovery that by using microfibril cellulose having an average fiber width of more than 1.0 μm to prepare a shatterproofing agent, the agent has shatterproofing effect while being resistant to gelling even when stored at high concentration, and can be made to a state in which it can be satisfactorily discharged by weak stirring even when diluting from a high concentration state to a concentration suitable for use.

[0011] <mfc> MFC is a fiber obtained by moderately beating or defibrating cellulose fibers using a refiner or the like to fibrillate them. MFC includes various sizes of fibers, such as fibers that have been moderately beaten or defibrated, with cellulose microfibril fluff visible on the surface, and fibers that have been defibrated to a fiber width on the submicron order. Unlike cellulose nanofibers (hereinafter, cellulose nanofibers will be referred to as "CNF") that have been highly defibrated to a nanoscale fiber width (for example, an average fiber width of 1000 nm or less), MFC includes fibers with a fiber width on the micron order.

[0012] The average fiber width of the MFC used in the present invention is greater than 1.0 μm. The average fiber width is more preferably 3.0 μm or more, and even more preferably 5.0 μm or more. By using an MFC that has been subjected to moderate fibrillation so as to maintain a certain average fiber width as a shatterproofing agent, it is possible to provide a shatterproofing agent that is less likely to gel even when stored at a high concentration, and can be made to be in a state where it can be discharged well even with weak stirring force when redispersed before use. The upper limit of the average fiber width is not particularly limited, but is about 25.0 μm or less, more preferably about 15.0 μm or less.

[0013] The average fiber length of MFC is not particularly limited, but is preferably 25 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more. The upper limit of the average fiber length is not particularly limited, but is preferably 3000 μm or less, more preferably 1500 μm or less, and even more preferably 1000 μm or less.

[0014] The average fiber width and average fiber length of MFC can be measured by the following method: 300 mL of the aqueous dispersion diluted to 0.1 g of MFC solid content is subjected to an image analysis type fiber analyzer (product name: L&W Fiber Tester Plus, manufactured by ABB) and measurements are performed for 300 seconds to determine the length-weighted average fiber width and average fiber length (n=2). Note that the measurement is performed after setting the Max value of Fines Limit to 0 and the Min value of Length class 1 to 0 on the Sample type screen that determines the measurement conditions.

[0015] The aspect ratio of MFC is preferably 5 or more, more preferably 10 or more. There is no particular upper limit to the aspect ratio, but it is preferably 1000 or less, more preferably 100 or less, and even more preferably 50 or less. When the aspect ratio is within this range, it is difficult for gelation to occur when stored at a high concentration, and it is advantageous in that it is easy to redisperse even with a relatively weak stirring force. The aspect ratio can be calculated by the following formula: Aspect ratio = average fiber length (μm) / average fiber width (μm) The cellulose fibers used as the raw material for obtaining MFC are not particularly limited, but examples thereof include those derived from plants, animals (e.g., ascidians), algae, and microorganisms (e.g., acetic acid bacteria (Acetobacter)). Examples of those derived from plants include cellulose fibers derived from wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, and pulp (softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), softwood dissolving pulp, hardwood dissolving pulp, recycled pulp, waste paper, etc.). Any one of these may be used, or two or more may be used in combination. Among these, cellulose fibers derived from plants or microorganisms are preferred, cellulose fibers derived from plants are more preferred, and cellulose fibers derived from wood pulp are even more preferred.

[0016] The average fiber width of the cellulose fibers used as the raw material is not particularly limited, but in the case of softwood kraft pulp, which is a common pulp, it is about 30 to 60 μm, and in the case of hardwood kraft pulp, it is about 10 to 30 μm. In the case of other pulps, those that have undergone general refinement have a width of about 50 μm. For example, when chips or the like having a size of several centimeters are used, it is preferable to mechanically treat them with a disintegrator such as a refiner or beater and adjust the average fiber width to about 50 μm before using them as the raw material for MFC.

[0017] <Fibrillation> MFC, which is a fibrillated cellulose fiber, can be obtained by appropriately beating or defibrating the cellulose fiber that is the raw material of MFC. The beating or defibration in the fibrillation is preferably performed in a wet manner (i.e., in the form of a dispersion in which water or the like is used as a dispersion medium) using a device such as a disk-type, conical-type, or cylinder-type refiner, a high-speed defibrator, a shear-type mixer, a colloid mill, a high-pressure jet disperser, a cavitation, a beater, a PFI mill, a kneader, or a disperser, but is not particularly limited to these devices, and any device that imparts mechanical defibration force in a wet manner may be used.

[0018] When performing wet fibrillation, first, a dispersion or slurry of cellulose fibers as a raw material is prepared. The solid content concentration in the dispersion or slurry of cellulose fibers to be subjected to fibrillation is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. The upper limit of the concentration is preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. The dispersion medium is preferably water.

[0019] The pH of the dispersion or slurry of cellulose fibers to be fibrillated is preferably 7.0 or less, more preferably 6.0 or less, and even more preferably 5.0 or less. There is no particular lower limit for the pH, and it is usually 2.0 or more, preferably 3.0 or more, and more preferably 3.5 or more. The pH can be adjusted by adding an acid such as hydrochloric acid.

[0020] Before preparing the dispersion or slurry to be subjected to fibrillation, the cellulose fibers as the raw material may be dried and pulverized in advance. The dry-pulverized raw material may then be dispersed in a dispersion medium and subjected to fibrillation (wet type). The device used for dry-pulverizing the raw material is not particularly limited, and examples thereof include impact mills such as hammer mills and pin mills, media mills such as ball mills and tower mills, and jet mills.

[0021] <Chemical modification> The MFC used in the present invention may be a chemically modified MFC in which cellulose has been chemically modified. Chemically modified MFC tends to be more easily dispersed uniformly in a solvent than unmodified MFC, and has a higher anti-scattering effect. Chemical modification may be applied to the raw cellulose fibers in advance, and the resulting cellulose fibers (i.e., the chemically modified cellulose fibers) may be subjected to the above-mentioned fibrillation (i.e., moderate beating or defibration) to produce a chemically modified MFC, or unmodified cellulose fibers may be fibrillated to produce an MFC, and then the MFC may be chemically modified to produce a chemically modified MFC. Since fibrillation is easier to proceed with chemically modified cellulose, it is preferable from the viewpoint of energy cost to chemically modify the raw cellulose fibers in advance to produce chemically modified cellulose fibers, and then fibrillate the resulting cellulose fibers to produce a chemically modified MFC.

[0022] The method of chemical modification is not particularly limited, but examples of chemical modifications include oxidation, etherification, phosphorylation, esterification, silane coupling, fluorination, and cationization. Among them, from the viewpoint of facilitating uniform dispersion in a solvent, oxidation (carboxylation), etherification, esterification, and cationization are preferred, and oxidation is particularly preferred. These will be described in detail below.

[0023] <Chemical modification - oxidation> An example of chemical modification is oxidation (carboxylation) in which a carboxyl group is introduced into a cellulose chain. In this specification, carboxylated cellulose fibers and carboxylated MFC may be referred to as "oxidized cellulose fibers" and "oxidized MFC". Oxidized cellulose fibers and oxidized MFC may be collectively referred to as "oxidized cellulose". The oxidized cellulose may be commercially available, or may be produced by oxidizing the above-mentioned cellulose raw material by a known method. The amount of carboxyl groups is preferably 0.1 to 2.5 mmol / g, more preferably 0.6 mmol / g to 2.5 mmol / g, and even more preferably 1.0 mmol / g to 2.0 mmol / g, based on the bone dry mass of the oxidized cellulose fibers or oxidized MFC. The amount of carboxyl groups can be measured by the following method: 60 mL of a 0.5% by mass slurry (aqueous dispersion) of the oxidized cellulose sample is prepared, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5. A 0.05 N aqueous sodium hydroxide solution is then added dropwise and the electrical conductivity is measured until the pH reaches 11. The electrical conductivity is calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual: Amount of carboxyl groups (mmol / g) = a (mL) × 0.05 / mass of oxidized cellulose sample (g).

[0024] The amount of carboxyl groups in the oxidized cellulose fibers before fibrillation is usually the same as the amount of carboxyl groups in the oxidized cellulose fibers after fibrillation (oxidized MFC).

[0025] One example of the oxidation method is a method in which the cellulose raw material is oxidized in water using an oxidizing agent in the presence of an N-oxyl compound and a compound selected from the group consisting of bromides, iodides, and mixtures thereof. This oxidation reaction selectively oxidizes the primary hydroxyl group at the C6 position of the glucopyranose ring on the cellulose surface, resulting in the formation of aldehyde groups and carboxyl groups (-COOH) or carboxylate groups (-COO - ) (carboxylated (oxidized) cellulose). The concentration of the cellulose raw material during the reaction is not particularly limited, but is preferably 5% by mass or less.

[0026] The term "N-oxyl compound" refers to a compound capable of generating nitroxy radicals. Any compound that can promote the target oxidation reaction can be used as the N-oxyl compound. Examples include 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO) and its derivatives (e.g., 4-hydroxyTEMPO). The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the cellulose raw material. For example, 0.01 to 10 mmol is preferable, 0.01 to 1 mmol is more preferable, and 0.05 to 0.5 mmol is even more preferable, per 1 g of bone-dry cellulose raw material. In addition, the amount is preferably about 0.1 to 4 mmol / L relative to the reaction system.

[0027] Bromides are compounds containing bromine, examples of which include alkali metal bromides that can dissociate and ionize in water. Also, iodides are compounds containing iodine, examples of which include alkali metal iodides. The amount of bromide or iodide used can be selected within a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 to 100 mmol, more preferably 0.1 to 10 mmol, and even more preferably 0.5 to 5 mmol, per 1 g of bone-dry cellulose raw material.

[0028] The oxidizing agent may be a known one, such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxide, peroxide, etc. Among them, sodium hypochlorite is preferable because it is inexpensive and has a low environmental impact. The appropriate amount of the oxidizing agent to be used is, for example, preferably 0.5 to 500 mmol, more preferably 0.5 to 50 mmol, further preferably 1 to 25 mmol, and most preferably 3 to 10 mmol, per 1 g of bone-dry cellulose raw material. Also, for example, 1 to 40 mol is preferable per 1 mol of the N-oxyl compound.

[0029] In the oxidation process of the cellulose raw material, the reaction proceeds efficiently even under relatively mild conditions. Therefore, the reaction temperature may be within the range of 4 to 40°C, or may be room temperature of about 15 to 30°C. As the reaction proceeds, carboxyl groups are generated in the cellulose chain, and therefore a decrease in the pH of the reaction solution is observed. In order to efficiently proceed with the oxidation reaction, it is preferable to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at about 8 to 12, preferably about 10 to 11. The reaction medium is preferably water, because it is easy to handle and does not easily cause side reactions. The reaction time in the oxidation reaction can be appropriately set according to the degree of progress of the oxidation, and is usually 0.5 to 6 hours, for example, about 0.5 to 4 hours.

[0030] The oxidation reaction may also be carried out in two stages. For example, the oxidized cellulose obtained by filtration after completion of the first-stage reaction can be oxidized again under the same or different reaction conditions, allowing efficient oxidation without reaction inhibition by table salt produced as a by-product in the first-stage reaction.

[0031] Another example of the oxidation method is a method in which the cellulose raw material is oxidized by contacting it with an ozone-containing gas. This oxidation reaction oxidizes at least the hydroxyl groups at positions 2 and 6 of the glucopyranose ring, and decomposes the cellulose chain. The ozone concentration in the ozone-containing gas is 50 to 250 g / m 3 It is preferable that the thickness is 50 to 220 g / m 3 The amount of ozone added to the cellulose raw material is preferably 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass, based on 100 parts by mass of the solid content of the cellulose raw material. The ozone treatment temperature is preferably 0 to 50°C, and more preferably 20 to 50°C. The ozone treatment time is not particularly limited, but is about 1 to 360 minutes, and preferably about 30 to 360 minutes. When the ozone treatment conditions are within these ranges, it is possible to prevent the cellulose raw material from being excessively oxidized and decomposed, and the yield of oxidized cellulose is good.

[0032] After the ozone treatment, an additional oxidation treatment may be performed using an oxidizing agent. The oxidizing agent used in the additional oxidation treatment is not particularly limited, and examples thereof include chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. For example, these oxidizing agents are dissolved in a polar organic solvent such as water or alcohol to prepare an oxidizing agent solution, and the additional oxidation treatment can be performed by immersing the cellulose raw material in the solution.

[0033] The amount of carboxyl groups in the oxidized cellulose fibers or oxidized MFC can be adjusted by controlling the reaction conditions, such as the amount of oxidizing agent added and the reaction time. <Chemical modification - Etherification> An example of chemical modification is etherification. Examples of etherification include CM modification in which a carboxymethyl group (hereinafter, "carboxymethyl" is referred to as "CM") is bonded to a cellulose chain via an ether bond, methylation in which a methyl group is bonded to an ether bond, ethylation with an ethyl group, cyanoethylation, hydroxyethylation, hydroxypropylation, ethylhydroxyethylation, and hydroxypropylmethylation. Among these, CM modification is described below as an example. In this specification, CM-modified cellulose fibers and CM-modified MFCs may be referred to as "CM-modified cellulose fibers" and "CM-modified MFCs." As the CM-modified cellulose fibers, commercially available ones may be used, or the above-mentioned cellulose raw material may be CM-modified by a known method. The CM substitution degree of cellulose is preferably 0.01 to 0.50. The upper limit is preferably 0.40 or less, and more preferably 0.35 or less. If the CM substitution degree exceeds 0.50, dissolution in water occurs easily, and the fiber form cannot be maintained in water. The CM substitution degree is more preferably 0.02 or more, more preferably 0.05 or more, and even more preferably 0.10 or more. The degree of CM substitution can be adjusted by controlling the amount of CM agent to be reacted, the amount of mercerizing agent, the composition ratio of water to organic solvent, and the like.

[0034] The degree of CM substitution (also called the degree of etherification) indicates the ratio of hydroxyl groups in the glucose residues that constitute cellulose that are substituted with CM ethers (the number of CM ethers per glucose residue). The degree of CM substitution is sometimes abbreviated as DS. The method for measuring the degree of CM substitution is as follows: Weigh out approximately 2.0 g of the sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of nitric acid methanol (a solution of 100 mL of concentrated nitric acid added to 1000 mL of methanol) and shake for 3 hours to convert the salt-type carboxymethylcellulose to hydrogen-type carboxymethylcellulose. Weigh out 1.5 to 2.0 g of hydrogen-type carboxymethylcellulose (absolutely dry) and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten with 15 mL of 80% methanol, add 100 mL of 0.1N NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1N H2SO4, and calculate the degree of carboxymethylcellulose substitution (DS) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (absolute dry mass of hydrogenated carboxylated cellulose (g)) CM substitution degree (DS)=0.162×A / (1-0.058×A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N NaOH.

[0035] The DS of the carboxylated cellulose fibers before fibrillation is usually the same as the DS of the carboxylated cellulose fibers after fibrillation (carboxylated MFC). The method for mercurizing the cellulose raw material is not particularly limited, but an example thereof is a method in which the cellulose raw material is mercerized and then etherified. Examples of the solvent used in the mercurization reaction include water, alcohol (e.g., lower alcohol), and a mixed solvent thereof. Examples of lower alcohol include methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, isobutanol, and tertiary butanol. When a mixed solvent is used, the mixing ratio of the alcohol is usually about 60 to 95 mass %. The amount of the solvent is usually about 3 to 20 times the mass of the cellulose raw material.

[0036] Mercerization is usually carried out by mixing the cellulose raw material with a mercerizing agent. Examples of the mercerizing agent include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide. The amount of the mercerizing agent used is preferably 0.5 to 20 times by mole, more preferably 1.0 to 10 times by mole, and even more preferably 1.5 to 5.0 times by mole, per anhydrous glucose residue of the cellulose raw material. The reaction temperature for mercerization is usually 0 to 70°C, preferably 10 to 60°C. The reaction time is usually 15 minutes to 8 hours, preferably 30 minutes to 7 hours.

[0037] The etherification reaction is usually carried out by adding a CM agent to the reaction system after mercerization. An example of the CM agent is sodium monochloroacetate. The amount of the CM agent added is preferably 0.05 to 10.0 times by mole, more preferably 0.5 to 5.0 times by mole, and even more preferably 0.8 to 3.0 times by mole, per glucose residue of the cellulose raw material. The reaction temperature is usually 30 to 90°C, preferably 40 to 80°C. The reaction time is usually 30 minutes to 10 hours, preferably 1 hour to 4 hours. If necessary, the reaction solution may be stirred during the CM reaction.

[0038] <Chemical modification - esterification> An example of chemical modification is esterification. As an example of esterification, phosphate esterification, which introduces phosphate groups into cellulose chains, will be described below. The phosphated cellulose fibers may be commercially available, or may be produced by phosphate esterifying the above-mentioned cellulose raw material by a known method. The degree of phosphate substitution per glucose unit of cellulose is preferably 0.001 or more and less than 0.40. The degree of phosphate substitution in the phosphated cellulose fibers before fibrillation is usually the same as the degree of phosphate substitution in the phosphated cellulose fibers after fibrillation (phosphated MFC).

[0039] Examples of the method of phosphate esterification include a method of mixing a powder or an aqueous solution of a compound having a phosphoric acid group with a cellulose raw material, and a method of adding an aqueous solution of a compound having a phosphoric acid group to a slurry of a cellulose raw material. Examples of the compound having a phosphoric acid group include phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium phosphite, potassium phosphite, sodium hypophosphite, potassium hypophosphite, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. Phosphate groups can be introduced into the cellulose raw material by using one or more of these in combination. Among these, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred from the viewpoints of high efficiency of phosphoric acid group introduction and easy industrial application. Sodium dihydrogen phosphate and disodium hydrogen phosphate are particularly preferred. In addition, it is desirable to use the compound having a phosphoric acid group as an aqueous solution, since the reaction can proceed uniformly and the efficiency of phosphoric acid group introduction is high. The pH of the aqueous solution of the compound having a phosphate group is preferably 7 or less since this increases the efficiency of introducing the phosphate group, but is preferably 3 to 7 from the viewpoint of suppressing hydrolysis of the fibers.

[0040] One example of a method for producing cellulose phosphate can be mentioned as follows. A compound having a phosphoric acid group is added to a suspension of a cellulose raw material having a solid content concentration of 0.1 to 10% by mass while stirring to introduce a phosphoric acid group into the cellulose. When the cellulose raw material is 100 parts by mass, the amount of the compound having a phosphoric acid group added is preferably 0.2 to 500 parts by mass, more preferably 1 to 400 parts by mass, in terms of the amount of phosphorus element. In this case, in addition to the compound having a phosphoric acid group, a powder or an aqueous solution of a nitrogen-containing compound exhibiting basicity may be mixed. "Exhibiting basicity" refers to a case where the aqueous solution exhibits a pink to red color in the presence of a phenolphthalein indicator, or a case where the pH of the aqueous solution is greater than 7. As the nitrogen-containing compound exhibiting basicity, a compound having an amino group is preferable. Examples include, but are not limited to, urea, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, urea, which is low-cost and easy to handle, is preferable. The amount of the nitrogen-containing compound exhibiting basicity added is preferably 2 to 1000 parts by mass, more preferably 100 to 700 parts by mass. The reaction temperature is preferably 0 to 95°C, more preferably 30 to 90°C. The reaction time is not particularly limited, but is about 1 to 600 minutes, more preferably 30 to 480 minutes. After the obtained suspension of phosphated cellulose is dehydrated, it is preferably heat-treated at 100 to 170°C from the viewpoint of suppressing hydrolysis of cellulose. Furthermore, during the heat treatment, it is preferably heated at 130°C or less, preferably 110°C or less while water is contained, and after the water is removed, it is preferably heat-treated at 100 to 170°C.

[0041] <Chemical modification - cationization> An example of chemical modification is cationization, which introduces cationic groups into cellulose chains. Cationized cellulose contains cations such as ammonium, phosphonium, and sulfonium in the molecule. Among these, it is preferable to contain a group having ammonium, and more preferable to contain a group having quaternary ammonium.

[0042] The method of cationization is not particularly limited, but may be, for example, a method of reacting a cationizing agent and a catalyst with a cellulose raw material in the presence of water and / or alcohol. Examples of the cationizing agent include glycidyl trimethylammonium chloride, 3-chloro-2-hydroxypropyl trialkylammonium hydride (e.g., 3-chloro-2-hydroxypropyl trimethylammonium hydride), or halohydrin types thereof, and by using any of these, cationized cellulose having a group containing quaternary ammonium can be obtained. Examples of the catalyst include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide. Examples of the alcohol include alcohols having 1 to 4 carbon atoms. The amount of the cationizing agent is preferably 5 to 800% by weight, more preferably 10 to 500% by weight, relative to 100% by weight of the cellulose raw material. The amount of the catalyst is preferably 0.5 to 7% by weight, more preferably 1 to 3% by weight, relative to 100% by weight of the cellulose fiber. The amount of the alcohol is preferably 50 to 50,000% by weight, more preferably 100 to 500% by weight, relative to 100% by weight of the cellulose fiber.

[0043] The reaction temperature during cationization is usually 10 to 90° C., preferably 30 to 80° C. The reaction time is usually 10 minutes to 10 hours, preferably 30 minutes to 5 hours. During the cationization reaction, the reaction solution may be stirred as necessary.

[0044] The degree of cationic substitution per glucose unit of cationized cellulose can be adjusted by controlling the amount of cationic agent added and the composition ratio of water and alcohol. The degree of cationic substitution indicates the number of substituents introduced per glucose residue (glucopyranose ring) constituting cellulose. In other words, the degree of cationic substitution is defined as "the value obtained by dividing the number of moles of the introduced substituents by the total number of moles of hydroxyl groups in the glucopyranose ring." Pure cellulose has three substitutable hydroxyl groups per unit structure (glucopyranose ring), so the theoretical maximum value of the degree of cationic substitution is 3 (the minimum value is 0).

[0045] The degree of cationic substitution of the cationized cellulose is preferably from 0.01 to 0.40, more preferably from 0.02 to 0.30, and further preferably from 0.03 to 0.20. The degree of cationic substitution can be measured by the following method: After drying the sample (cationized cellulose), the nitrogen content was measured using a total nitrogen analyzer TN-10 (manufactured by Mitsubishi Chemical Corporation), and the degree of cationization was calculated using the following formula: Degree of cation substitution = (162 x N) / (1-151.6 x N) N: Nitrogen content.

[0046] <Transparency> The MFC used in the present invention, when dispersed in water at a concentration of 1.0% by mass, preferably has a transmittance (hereinafter referred to as "transparency") of light with a wavelength of 660 nm of 60% or less, more preferably 50% or less, and even more preferably 45% or less. There is no particular lower limit, and it may be 0% or more. The transparency can be measured by the following method: An aqueous dispersion of MFC (solid content concentration: 1.0% by mass) is prepared, and the transmittance of light with a wavelength of 660 nm is measured using a UV-VIS spectrophotometer UV-1800 (manufactured by Shimadzu Corporation) with a square cell having an optical path length of 10 mm.

[0047] <Crystallization degree of cellulose type I> The crystallinity of the cellulose in the MFC used in the present invention is preferably 50% or more, more preferably 60% or more, for crystalline type I. There is no particular upper limit, and it may be 100% or less. Natural cellulose is type I cellulose, and when the MFC is unmodified, it usually shows type I cellulose. In the case of chemically modified MFC, in order to maintain cellulose type I crystals, it is preferable to use cellulose having a high degree of crystallinity of type I cellulose as the raw material. The crystallinity of type I cellulose of the cellulose raw material when obtaining chemically modified MFC is preferably 70% or more, more preferably 80% or more. The crystallinity of type I cellulose can be measured by the following method: The sample is placed in a glass cell and measured using an X-ray diffraction measuring device (product name: LabX XRD-6000, manufactured by Shimadzu Corporation). The degree of crystallinity is calculated using the method of Segal et al., and is calculated from the diffraction intensity of the 002 plane at 2θ = 22.6° and the diffraction intensity of the amorphous part at 2θ = 18.5° using the diffraction intensity of the X-ray diffraction pattern at 2θ = 10° to 30° as the baseline, according to the following formula.

[0048] Xc = (I002c - Ia) / I002c x 100 Xc = Crystallinity of cellulose type I (%) I002c: 2θ=22.6°, diffraction intensity of 002 plane Ia: 2θ=18.5°, diffraction intensity of the amorphous part.

[0049] <Solvent> The shatterproofing agent of the present invention contains the above-mentioned MFC and a solvent. In consideration of the impact on the environment and the affinity with MFC, the solvent is preferably one that contains water as a main component. That is, when the entire solvent is taken as 100 mass%, it is preferable that the solvent contains 50 mass% or more of water. More preferably, the water content is 70 mass% or more, and even more preferably, 90 mass% or more. The solvent may be only water (100 mass%).

[0050] Examples of the solvent that may be used in the case where a solvent other than water is contained include, but are not limited to, organic solvents. Examples of the organic solvent include alcohol solvents such as methanol, ethanol, 1-propanol, 2-propanol, isopropanol, n-butanol, isobutanol, salicyl alcohol, cinnamyl alcohol, veraryl alcohol, cinnabyl alcohol, diphenylmethanol, vanillyl alcohol, benzyl alcohol, 2-methylbenzyl alcohol, 3-methylbenzyl alcohol, 3-nitrilebenzyl alcohol, 4-methylbenzyl alcohol, α-methylbenzyl alcohol, allyl alcohol, propargyl alcohol, phenethyl alcohol, hydroxybenzyl alcohol, and hydroxyphenethyl alcohol; ethylene glycol derivatives such as ethylene glycol, ethylene glycol monobutyl ether, and ethylene glycol monoethyl ether acetate; and diethylene glycol derivatives such as diethylene glycol and diethylene glycol monobutyl ether. diacetone alcohol; pyrrolidone compounds such as 2-pyrrolidone, 3-pyrrolidone, N-alkyl-2-pyrrolidone (e.g., N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-propyl-2-pyrrolidone), 5-alkyl-2-pyrrolidone (e.g., 5-methyl-2-pyrrolidone, 5-ethyl-2-pyrrolidone, 5-propyl-2-pyrrolidone), N-vinyl-2-pyrrolidone, and N-alkyl-3-pyrrolidone (e.g., N-methyl-3-pyrrolidone, N-ethyl-3-pyrrolidone, N-propyl-3-pyrrolidone); nitrogen-containing solvents such as formamide, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide; and chlorine-based solvents such as chloroform, carbon tetrachloride, methylene chloride, trichloroethylene, and tetrachloroethylene.

[0051] <Anti-scattering agent> The shatterproofing agent of the present invention contains the above-mentioned MFC and a solvent. The concentration of MFC in the shatterproofing agent is preferably about 0.5 to 2.5 mass%, more preferably about 0.5 to 1.5 mass%, at the time of use of the shatterproofing agent. However, as described below, the shatterproofing agent of the present invention is unlikely to gel even when stored at a high concentration, and can be dispersed well with weak stirring even when diluted to an appropriate concentration at the time of use. Therefore, during transportation or storage before use, the MFC may be kept at a higher concentration, for example, a concentration of more than 2.5 mass%, more preferably a concentration of 3.0 mass% or more.

[0052] The shatterproofing agent of the present invention may contain components other than MFC and the solvent, as long as the effects of the present invention are not impaired. Examples of such components include surfactants, antifoaming agents, antioxidants, stabilizers, preservatives, etc. When such components are contained, the content of these components is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the shatterproofing agent.

[0053] The scattering prevention agent of the present invention can be used to prevent scattering of soil or sand scattered from the ground surface, dust scattered from construction sites, mining sites for metals, reclaimed land, construction sites, waste disposal sites, various factories, etc., and fine particles such as PM2.5. It can also be used to prevent scattering of mulching materials used in agricultural land, etc.

[0054] Mulching materials are materials for covering the ground surface of plants to prevent the growth of weeds, drying due to evaporation of water, the growth of pests, etc. As mulching materials, artificial or inorganic materials (artificial mulching materials) such as vinyl sheets, woven fabrics, nonwoven fabrics, colored plastics, crushed stones, gravel, pebbles, crushed blocks, asphalt, mortar, and waste rubber are used. In addition, as an alternative to artificial mulching materials, organic mulching materials (organic mulching materials) such as straw mulch, tea leaves, bark, branches and leaves, wood chips, waste wood chips, bamboo chips, sawdust, rice straw, wheat straw, herbaceous stems (Japanese silver grass, reeds, Imperata cylindrica, etc.), lawn mowing, rice husks, corn cob husks, coffee husks, crushed oyster shells, shells, and rice bran are also used. The scattering prevention agent of the present invention can also be used as a scattering prevention agent for these mulching materials laid on agricultural land such as fields. Among them, organic mulching materials are preferable as targets for the scattering prevention agent of the present invention. Organic mulching materials are environmentally friendly materials that have attracted attention from the viewpoint of effective use of agricultural residues, food residues, etc. and from the viewpoint of eliminating the use of plastics, and also have the advantage that when the materials are no longer needed, such as after harvesting crops, they can be directly ploughed into the soil, and there is no need to collect and dispose of them. The scattering prevention agent of the present invention uses a material derived from cellulose (MFC), so it has the advantage of being less burdensome to the environment and being able to be ploughed into the soil together with the materials when plowing the materials into the soil.

[0055] <How to prevent scattering> By spraying the anti-scattering agent of the present invention on the above-mentioned objects, it is possible to obtain an anti-scattering effect on the objects. The method of spraying is not particularly limited, and examples thereof include a method of spraying with a sprayer such as a mister, an electric sprayer, or an engine-powered sprayer, a method of spraying from a nozzle while circulating with a pump, and a method of spraying a certain amount at once with a watering can or a ladle. The amount of spraying may be appropriately adjusted depending on the object and the environment, but for example, 0.3 to 3.0 L / m 2 Approximately, more preferably 0.5 to 2.0 L / m 2 The amount of MFC to be sprayed may be adjusted appropriately depending on the object and environment, but is, for example, 1 to 20 g / m 2 More preferably, 3 to 15 g / m 2 That's about it.

[0056] The shatterproofing agent of the present invention is characterized in that it is difficult to gel even when stored at a high concentration, and can be well dispersed with weak stirring even when diluted to an appropriate concentration when used. Therefore, it is possible to keep the MFC at a high concentration when transporting or storing, and dilute it to an appropriate concentration at the site when using. In this way, the cost of transportation and storage can be reduced. For example, when transporting or storing, the MFC may be kept at a concentration higher than 2.5 mass%, more preferably at a concentration of 3.0 mass% or more, and left in this state for a while, and then diluted to a concentration suitable for use, for example, 0.5 to 2.5 mass%, more preferably 0.5 to 1.5 mass%, before use. The period of storage is not particularly limited. For example, it is at least 30 minutes or more, and may be several days. There is no need to perform a stirring process during storage. When diluting, stirring is preferably performed, but the stirring at this time may be weak stirring. For example, it may be manual stirring or stirring at about pump pressure (circulation stirring), or when a rotary stirrer is used, it may be stirring at 100 to 2500 rpm for about 5 to 120 seconds. In many cases, the site where the anti-scattering agent is used does not have equipment capable of performing strong stirring or strong dispersion treatment. However, the anti-scattering agent of the present invention can be easily diluted and redispersed for use even in such a site, which is advantageous in terms of cost and workability. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, parts and % indicate parts by mass and % by mass.

[0058] (MFC manufacturing) 40 kg (bone-dry) of bleached unbeaten kraft pulp (brightness 85%: Nippon Paper Industries Co., Ltd.) derived from conifers was added to 4000 L of an aqueous solution containing 312 g (0.05 mmol per 1 g of bone-dry cellulose) of TEMPO (Sigma Aldrich) and 4112 g (1.0 mmol per 1 g of bone-dry cellulose) of sodium bromide, and the mixture was stirred until the pulp was uniformly dispersed. Aqueous sodium hypochlorite solution was added to the reaction system so that the sodium hypochlorite concentration was 5.5 mmol / g, and the oxidation reaction was started at room temperature. The pH of the system decreased during the reaction, but 3M aqueous sodium hydroxide solution was added successively to adjust the pH to 10. The reaction was terminated when the sodium hypochlorite was consumed and the pH of the system no longer changed. After adding hydrochloric acid to the reaction mixture to adjust the pH to 2, the pulp was thoroughly washed by repeatedly dehydrating and diluting with water, and finally dehydrated until the pulp solid content concentration was 20 mass%, to obtain chemically modified pulp (oxidized cellulose fiber). The pulp yield was 90%, and the amount of carboxyl groups was 1.41 mmol / g. The obtained oxidized cellulose fiber with a solid content concentration of 20 mass% was dispersed in tap water, and then sodium hydroxide was added and stirred to obtain an aqueous dispersion of oxidized pulp with a pH of 7.6 and a solid content concentration of 4.6 mass%. 80 kg of the obtained aqueous dispersion of oxidized cellulose fiber was beaten for 14 minutes using a Lab Refiner (manufactured by Aikawa Iron Works) to obtain oxidized MFC. The number of passes in the beating process was 20. The average fiber width was 9.6 μm, and the average fiber length was 138 μm.

[0059] (CNF manufacturing) The oxidation reaction was carried out in the same manner as in the production of MFC, and the reaction was terminated when the pH in the system no longer changed. The mixture after the reaction was filtered through a glass filter to separate the pulp, and the pulp was thoroughly washed with water to obtain chemically modified pulp (oxidized cellulose fiber). This was adjusted to a solid content concentration of 1.0 mass% with water and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain an oxidized CNF dispersion. The number average fiber width of the oxidized CNF measured with a transmission electron microscope was 3 nm, and the aspect ratio was 250.

[0060] (Example 1: Preparation of spray solution 1) Using the MFC and CNF produced above, tests were conducted to produce spray solutions for preventing scattering.

[0061] First, a 3.0% by mass aqueous dispersion of MFC or CNF was prepared. The day after preparing these dispersions, five times the amount of tap water was added to each dispersion to make the concentration about 0.5% by mass, and the container was lightly shaken by hand to stir. Furthermore, it was stirred at 1000 rpm for 30 seconds using a homodisper.

[0062] A portion of the resulting MFC dispersion and CNF dispersion, each with a concentration of approximately 0.5% by mass, was transferred to a petri dish to confirm the state of dispersion. The results are shown in Figure 1. As shown in the photograph in Figure 1, many gel lumps remained in the CNF dispersion, while the MFC dispersion contained air bubbles but was a homogeneous liquid.

[0063] In addition, MFC dispersions and CNF dispersions with a concentration of about 0.5% by mass were placed in a spray bottle and sprayed. The CNF dispersion could not be sprayed in its entirety because gel remained, but the MFC dispersion could be sprayed in its entirety without clogging. From these results, it was found that the MFC dispersion can be made into a liquid that can be sprayed well even with weak stirring such as 1000 rpm for 30 seconds, and that a spray liquid for preventing scattering can be produced with simpler operations than the CNF dispersion.

[0064] (Example 2: Preparation of spray solution 2) Using the MFC produced above, a 3.0% by mass aqueous dispersion of MFC was prepared. The next day, tap water was added to the dispersion to make the concentration 1.2% by mass, and the container was lightly shaken by hand to stir. Furthermore, the mixture was stirred at 1000 rpm for 60 seconds using a homodisper.

[0065] A portion of the obtained MFC dispersion with a concentration of 1.2% by mass was transferred to a petri dish, and the dispersion state was confirmed. Although it contained air bubbles, it was a homogeneous liquid. In addition, when a 1.2% by mass MFC dispersion was placed in a spray bottle and sprayed, the entire amount was sprayed without clogging. This result shows that even with a 1.2% by mass MFC dispersion, it is possible to prepare a spray liquid that can be sprayed well by performing weak stirring such as at 1000 rpm for 60 seconds.

[0066] (Example 3: Soil scattering prevention test) The soil (product name: Flower and Vegetable Soil, manufactured by Akagi Engei Co., Ltd.) was air-dried and passed through a 4.5 cm sieve, and the soil that passed through was used as the object to be prevented from scattering.

[0067] Containers (166mm x 106mm x 86mm) were prepared, and the mass of each container (container mass) was measured. 3-4cm of soil was placed in each container, and it was then compacted by poking it with a 180g ram. This was done three times, and approximately 700g of soil was packed into the containers. The mass of each container after the soil was packed was measured, and the mass of the soil packed into each container was calculated by subtracting the previously measured container mass.

[0068] An MFC dispersion with a concentration of about 0.5% by mass was prepared by the method described in Example 1. Also, an MFC dispersion with a concentration of 1.0% by mass was prepared by the same method as in Example 2, except that the concentration was changed to 1.0% by mass. Also, as a reference example, a CNF dispersion with a concentration of about 0.5% by mass was prepared by the same method as in Example 1, except that strong stirring was added for 60 seconds at 3000 rpm using a homodisper. Each of these dispersions was used as a spray liquid for preventing soil from scattering.

[0069] Water, MFC dispersion, and CNF dispersion were sprayed onto the soil packed in a container using a spray bottle. Each dispersion was used immediately after preparation. The spray volume was 1 L / m. 2 or 2 L / m 2 The amount of soil per container was either 17.6g or 35.2g. After spraying, the containers were left indoors for two days. After leaving the containers for two days, the mass of each container was measured, and the mass of the soil in each container (before blowing air) was calculated by subtracting the previously measured mass of the container.

[0070] Next, a blower (product name: Blower GBL800E, manufactured by Bosch) was used to blow air at the surface of the soil for 5 minutes at a speed of 15 m / s. After blowing, the mass of each container was measured, and the mass of the soil in each container after blowing was calculated by subtracting the mass of the container measured beforehand.

[0071] The amount of soil scattered was calculated by subtracting the mass of soil after the air blowing from the mass of soil before the air blowing. The scattering rate was calculated using the following formula: Scattering rate (%) = (scattering amount (g) / mass of soil before blowing (g)) x 100 The results are shown in Table 1.

[0072] [Table 1]

[0073] The results in Table 1 show that the anti-scattering spray liquid of the MFC dispersion can obtain the same anti-scattering effect as the anti-scattering spray liquid of the CNF dispersion. As shown in Example 1, compared to the CNF dispersion, the MFC dispersion can prepare a liquid that can be discharged well even with weak stirring, so it can be easily used at sites where scattering of dust such as soil is actually prevented, which is advantageous.

[0074] (Example 4: Test to prevent scattering of organic mulch materials) Using the same soil and containers as in Example 3, the soil was filled 3-4 cm deep and compacted by poking with a 180 g ram. This was done three times, and the soil was packed so that the depth from the edge of the opening side of the container to the surface of the soil was 28 mm. The mass of the soil packed in each container was calculated using the same method as in Example 3.

[0075] Organic mulch materials such as dried roasted green tea leaves or straw were laid on top of the soil so that the soil was leveled off in the containers. The mass of the organic mulch materials laid in each container was calculated.

[0076] An MFC dispersion with a concentration of about 0.5% by mass was prepared by the method described in Example 1 and used as a spray liquid for preventing scattering of organic mulch materials. Water or MFC dispersion was sprayed onto the organic mulch material laid in the container. The MFC dispersion was used immediately after preparation. The spray rate was 1 L / m. 2 or 2 L / m 2 After spraying, the containers were left indoors for two days. After leaving them for two days, the mass of each container was measured, and the mass of the contents in each container (mass before blowing air) was calculated by subtracting the previously measured mass of the container.

[0077] Next, air was blown against the surfaces of the containers for 5 minutes at a speed of 15 m / s using a blower, in the same manner as in Example 3. After blowing, the mass of each container was measured, and the mass of the contents in each container after blowing (mass after blowing) was calculated by subtracting the container mass measured beforehand.

[0078] The amount of scattered contents was calculated by subtracting the mass after the air blowing from the mass before the air blowing. The scattering rate was calculated using the following formula: Scattering rate (%) = (scattering amount (g) / mass before blowing (g)) x 100 The results are shown in Table 2. Also, photographs of each container after blowing air are shown in Figure 2.

[0079] [Table 2]

[0080] From the results in Table 2 and Figure 2, it can be seen that spraying the MFC dispersion onto organic mulch material laid on soil can prevent the organic mulch material and soil from scattering. These results show that the MFC dispersion can be used as a spray liquid to prevent the scattering of organic mulch material.

[0081] The scattering prevention agent of the present invention is environmentally friendly because it uses a material derived from cellulose. When organic mulching materials are no longer needed after harvesting, they do not need to be collected or disposed of, and can simply be worked into the soil. The scattering prevention agent of the present invention can also be worked into the soil together with the organic mulching materials.< / mfc>

Claims

1. A shatterproofing agent comprising microfibril cellulose having an average fiber width of greater than 1.0 μm and a solvent.

2. The shatterproofing agent according to claim 1 , wherein the microfibril cellulose is chemically modified microfibril cellulose.

3. 3. The shatterproof agent according to claim 1, wherein the microfibril cellulose has a transmittance of 60% or less for light having a wavelength of 660 nm when dispersed in water at 1.0% by mass.

4. The shatterproofing agent according to claim 1 or 2, wherein the solvent contains water in an amount of 50% by mass or more when the entire solvent is taken as 100% by mass.

5. The shatterproof agent according to claim 1 or 2, comprising 0.5 to 2.5 mass% of the microfibril cellulose.

6. The scattering prevention agent according to claim 1 or 2, for preventing scattering of organic mulch materials.

7. Providing microfibril cellulose having an average fiber width of greater than 1.0 μm; Preparing a dispersion containing the microfibril cellulose at a concentration of more than 2.5% by mass; The dispersion is allowed to stand for 30 minutes or more without stirring. diluting the dispersion that has been left standing so that the concentration of the microfibril cellulose is 0.5 to 2.5% by mass, and stirring the diluted dispersion; and The dispersion liquid after the stirring process is sprayed toward an object to be prevented from scattering. A shatterproof method comprising:

8. Use of microfibril cellulose having an average fiber width of more than 1.0 μm for producing a shatterproof agent.

Citation Information

Patent Citations

  • Fiber-mixed emulsion for mixing in soil material

    JP1995331241A

  • Method for recovering propylene glycol

    JP2013082672A

  • Dust preventing agent and solidification method thereof

    JP2013082872A

  • Agent for preventing scattering of dust and method for preventing scattering of dust

    JP2021155738A